Glycoprotein 5 Is Cleaved by Cathepsin E during Porcine Reproductive and Respiratory Syndrome Virus Membrane Fusion - Hou, Jie (J Virol, 2020)
Porcine reproductive and respiratory syndrome (PRRS) is a serious viral disease affecting the global swine industry. Its causative agent, PRRS virus (PRRSV), is an enveloped virus, and therefore membrane fusion between its envelope and host cell target membrane is critical for viral infection. Though much research has focused on PRRSV infection, the detailed mechanisms involved in its membrane fusion remain to be elucidated. In the present study, we performed confocal microscopy in combination with a constitutively active (CA) or dominant negative (DN) mutant, specific inhibitors, and small interfering RNAs (siRNAs), as well as multiple other approaches, to explore PRRSV membrane fusion. We first observed that PRRSV membrane fusion occurred in Rab11-recycling endosomes during early infection using labeled virions and subcellular markers. We further demonstrated that low pH and cathepsin E in Rab11-recycling endosomes are critical for PRRSV membrane fusion. Moreover, PRRSV glycoprotein 5 (GP5) is identified as being cleaved by cathepsin E during this process. Taken together, our findings provide in-depth information regarding PRRSV pathogenesis, which support a novel basis for the development of antiviral drugs and vaccines. IMPORTANCE PRRS, caused by PRRSV, is an economically critical factor in pig farming worldwide. As PRRSV is a lipid membrane-wrapped virus, merging of the PRRSV envelope with the host cell membrane is indispensable for viral infection. However, there is a lack of knowledge on its membrane fusion. Here, we first explored when and where PRRSV membrane fusion occurs. Furthermore, we determined which host cell factors were involved in the process. Importantly, PRRSV GP5 is shown to be cleaved by cathepsin E during membrane fusion. Our work not only provides information on PRRSV membrane fusion for the first time but also deepens our understanding of the molecular mechanisms of PRRSV infection, which provides a foundation for future applications in the prevention and control of PRRS.